Understanding visitor interaction with a projection augmented relief model display: insights from an in-the-wild study in the English Lake District - Priestnall, Gary; Cheverst, Keith (Personal and Ubiquitous Computing, 2022)
Projection augmented relief models (PARMs) are a promising tangible display technology for assisting users in orientating themselves within the represented landscape. The production of physical models is now easier than ever thanks to more freely available digital terrain data and 3D fabrication technology. When placed in a public setting, such as a visitor centre, the physical nature of such displays coupled with digital surface projection is compelling, enticing passers-by to notice and interact playfully with the display. In this article, we describe findings from our in-the-wild study of a PARM display designed to engage and orient visitors to the rural landscape of a remote valley in the heart of the English Lake District. The deployment has involved close collaboration with the Lake District National Trust, and the results of our 3-day observation study (n = 221) contribute to the growing research community seeking to explore and uncover technology designs that are both playful and unobtrusive to the nature experience. Our research also contributes to the literature on public and situated digital displays and, in particular, understandings of visitor behaviour as considered through the so-called audience funnel framework. Our observations revealed that a significant portion (79%) of visitors noticed the PARM display and that, of these, 68% transitioned to giving the display their focal attention. We also observed an apparent expectation for the PARM display to support direct tangible interaction (such as pointing gestures) which contrasts to the phenomenon of interaction blindness discussed in the literature.